Current Trends in E-Learning Development - Zoltan Zakota (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
E-learning, electronic or digital education, is one of the areas in which information and communication technologies, if although not in the most spectacular way, but have certainly had the deepest impact. All that first seemed to be just an extension of distance learning, and then of the so-called computer-assisted education, has now become an independent, ever-expanding and increasingly dynamic industry. ELearning tools are now used at all levels and in all areas of education and training, including non-formal and lifelong extensions. The aim of my study is to present the current trends in this extremely fast-moving and enormously innovative area. When outlining trends, I take into account the opinions and forecasts of leading individuals, companies and organizations in the profession and the industry.
Keywords: P46; I21; N30; 330; education; training; E-learning; digital education; ICT; trend forecast